2018
DOI: 10.3390/atmos9080306
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Bärfuss et al. New Setup of the UAS ALADINA for Measuring Boundary Layer Properties, Atmospheric Particles and Solar Radiation. Atmosphere, 2018, 9, 28

Abstract: The authors would like to correct the published article [1] concerning acknowlegdements as follows[...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…However, the direct observations of surface fluxes at similar scales to remote-sensing or process-based models are lacking, which restricts the study and development of simulations of regional and global surface fluxes [ 10 ]. Therefore, the regional-scale observation is considered the missing scale in the study of global surface flux [ 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the direct observations of surface fluxes at similar scales to remote-sensing or process-based models are lacking, which restricts the study and development of simulations of regional and global surface fluxes [ 10 ]. Therefore, the regional-scale observation is considered the missing scale in the study of global surface flux [ 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the advances in unmanned aerial vehicle (UAV) technology, as well as micro-electro-mechanical systems (MEMS), global positioning system (GPS), and batteries, have enabled the UAV to carry smaller, faster and more energy-efficient observation instruments for ecosystem studies [ 12 , 24 ]. Compared to manned aircraft, unmanned and automatically operating aircrafts have minimal logistical requirements (e.g., no airport is necessary), and are more flexible, cheaper to operate and maintain, and are less disturbance to turbulence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More information on the airplane itself can be found in Altstädter et al (2015). The instrumentation was updated for DACCIWA and the set-up is provided in Bärfuss et al (2018). All UAS data derived during DACCIWA are available from Bärfuss et al (2017).…”
mentioning
confidence: 99%
“…A detailed description of the airplane is given in Altstädter et al (2015) and information 30 on the new set-up can be found in Bärfuss et al (2017). The payload on ALADINA is equipped with aerosol instrumentation and meteorological sensors with high temporal resolution.…”
mentioning
confidence: 99%